2013
DOI: 10.1111/eje.12071
|View full text |Cite
|
Sign up to set email alerts
|

Using an audience response system to improve learning success in practical skills training courses in dental studies – a randomised, controlled cross‐over study

Abstract: The results indicate that the use of the ARS leads to better results in cognitive performance, especially where independent learning is required and should be encouraged. Weaker students in particular seem to benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Other studies radiographically assessed only the length and density of root canal filling but omitted the taper variable [1417]. We incorporated the taper variable defined by guidelines [18] and results were comparable to other research studying tapers [5, 14, 15, 19]. We observed adequate taper in 68.8% of root canals, a finding slightly less than the 71% reported by Román-Richon and colleagues, in which rotary files were used and 82% were reported by Fonseka and colleagues, of which the latter study only investigated single-rooted molars with wide versus narrow canals [15, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies radiographically assessed only the length and density of root canal filling but omitted the taper variable [1417]. We incorporated the taper variable defined by guidelines [18] and results were comparable to other research studying tapers [5, 14, 15, 19]. We observed adequate taper in 68.8% of root canals, a finding slightly less than the 71% reported by Román-Richon and colleagues, in which rotary files were used and 82% were reported by Fonseka and colleagues, of which the latter study only investigated single-rooted molars with wide versus narrow canals [15, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Real time interactive device are called many different names in instruction related literature; audience response system is the most frequently used (Hunsu, Adesope, & Bayly, 2016;Wenz, Zupanic, Klosa, Schneider, & Karsten, 2014), followed by electronic voting system (Cubric & Jefferies, 2015;Draper & Brown, 2004), electronic response system (Donovan, 2007;Ghosh & Renna, 2009), personal response system (Lin et al, 2013;Yeh & Tao, 2013), student response system (Hooker, Denker, Summers, & Parker, 2016;Jones, Antonenko, & Greenwood, 2012), clickers (Hwang, Wong, Lam, & Lam, 2015;King, 2011), classroom response system (Chien, Lee, Li, & Chang, 2015;Richardson, Dunn, McDonald, & Oprescu, 2015), interactive response system (Y. Kim et al, 2015;Slain, Abate, Hodges, Stamatakis, & Wolak, 2004), and instant response system (Chien, Chang, & Chang, 2016;Chien et al, 2015).…”
Section: Interactive Response System -Plickersmentioning
confidence: 99%
“…11,[14][15][16][17][18][19][20][21] Interactivity has been demonstrated to increase motivation and keep the attention of students for longer. 1,2,6,22-26 Wessels et al demonstrated that students who had interactive lectures felt more attentive, and they felt that their knowledge acquisition improved.…”
Section: Discussionmentioning
confidence: 99%
“…2,14,17,18,[27][28][29][30][31][32][33][34] LAP provides instant feedback to students in the form of graphs which are displayed both to the students and lecturer. We believe this keeps the audience's interest better than traditional lecturers, and this was reflected in the survey responses ( figure 3B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation